Pemberdayaan Ekonomi Masyarakat Melalui Home Industri Tenunan Kain Buton Kota Baubau - Iin Septianingsih (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Community empowerment is aimed at people or groups who are vulnerable and weak so that they have the ability to fulfill basic needs, reach productive sources, and participate in development. Community empowerment is one of the factors that determines the economic development of a region. One of the national development targets is to reduce social disparities in society and increase the rate of economic growth. This research aims to determine the effectiveness of the Community Empowerment Program through Home Industry Businesses. This type of research is field research and is descriptive. Data collection methods include primary data and secondary data. The results of the research explain that efforts to empower the Baubau city community are carried out by disseminating educational activities and training that can increase insight and interest in entrepreneurship. Apart from that, the local government also distributes capital assistance to people who need capital through creative economic activities to carry out development of the MSME sector.